WIT AND WITHDRAWAL: COMIC IRONY IN CHATTERJEE’S BUREAUCRATIC INDIA - Shashidhara S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the complex interplay of comic irony and existential withdrawal in Upamanyu Chatterjee’s English, August: An Indian Story, a seminal work in postcolonial Indian English fiction. At its core, the novel presents a scathing yet humorous portrayal of India’s bureaucratic machinery through the eyes of Agastya Sen, a young civil servant who is simultaneously bemused, alienated, and entrapped by the absurdity of his surroundings. Chatterjee employs a dry, sardonic tone to expose the monotony, inefficiency, and performative seriousness of postcolonial administration, while also offering a deeply introspective look at the psychological retreat of the protagonist. The comic irony functions not merely as satire but also as a mode of resistance, both to the legacy of colonial governance and to the existential crisis of a Western-educated Indian in a provincial Indian town. Through Agastya’s passive detachment and inner commentary, the novel underscores the futility of imposed roles and the absurdity of identity caught between cultural binaries. This paper argues that humour, far from being superficial, becomes a subversive tool that reveals both personal and political truths about modern Indian life and governance.